Advanced Time-Correlated Single Photon Counting Techniques - Becker, Wolfgang; Castleman, A. W.; Toennies, J.P.; Zinth, W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Time-correlated single photon counting (TCSPC) is a remarkable technique for recording low-level light signals with extremely high precision and picosecond-time resolution. TCSPC has developed from an intrinsically time-consuming and one-dimensional technique into a fast, multi-dimensional technique to record light signals. So this reference and text describes how advanced TCSPC techniques work and demonstrates their application to time-resolved laser scanning microscopy, single molecule spectroscopy, photon correlation experiments, and diffuse optical tomography of biological tissue. It gives practical hints about constructing suitable optical systems, choosing and using detectors, detector safety, preamplifiers, and using the control features and optimising the operating conditions of TCSPC devices. Advanced TCSPC Techniques is an indispensable tool for everyone in research and development who is confronted with the task of recording low-intensity light signals in the picosecond and nanosecond range.
Optical Signal Recording -- Overview of Photon Counting Techniques -- Multidimensional TCSPC Techniques -- Building Blocks of Advanced TCSPC Devices -- Application of Modern TCSPC Techniques -- Detectors for Photon Counting -- Practice of TCSPC Experiments -- Final Remarks -- References.
Keywords: Physics; Physical chemistry; Solid state physics; Lasers; Photonics; Optics; Optoelectronics; Plasmons (Physics).; Spectroscopy; Microscopy; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Physical Chemistry; Solid State Physics; Spectroscopy and Microscopy; Laser Technology, Photonics; Electronic books